2014
DOI: 10.1016/j.pupt.2014.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Specific subsets of mesenchymal stroma cells to treat lung disorders – Finding the Holy Grail

Abstract: Accumulating studies, both in animals and human clinical trials with mesenchymal stroma cells (MSC) support the hypothesis of therapeutic effects of these cells in various disorders. However, despite success in immune-mediated disorders such as Crohns' disease, lung disorders such as chronic obstructive pulmonary disease (COPD) and idiopathic pulmonary disease (IPF) treated with MSC have so far not yielded a revolutionary effect on clinical symptoms. Promising data on immunomodulatory effects in COPD have kept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…To date, accumulating evidence from clinical trials shows that intravenous or endobronchial transplantation of MSCs in humans is safe. Moreover, MSCs have been reported to exert beneficial effects in phase 1 and 2 clinical trials in immunemediated diseases, such as graft-versus-host disease and Crohn's disease [178]. In a phase 1b, nonrandomized clinical trial in 14 IPF patients, there were no serious adverse events within 12 months after 3 endobronchial infusions of autologous ADSCs [179].…”
Section: Clinical Trials With Stem Cells In Ipfmentioning
confidence: 99%
“…To date, accumulating evidence from clinical trials shows that intravenous or endobronchial transplantation of MSCs in humans is safe. Moreover, MSCs have been reported to exert beneficial effects in phase 1 and 2 clinical trials in immunemediated diseases, such as graft-versus-host disease and Crohn's disease [178]. In a phase 1b, nonrandomized clinical trial in 14 IPF patients, there were no serious adverse events within 12 months after 3 endobronchial infusions of autologous ADSCs [179].…”
Section: Clinical Trials With Stem Cells In Ipfmentioning
confidence: 99%
“…Certain types of stem cell such as hematopoietic stem cell transplants have been proven to provide effective treatment for leukemia, lymphoma, or severe combined immunodeficiency. Additionally, in phase I and II clinical trials mesenchymal or stromal cells (MSCs) have been reported to exert beneficial effects on immune- mediated diseases such as graft-versus-host disease and Crohn disease [1]. …”
Section: Introductionmentioning
confidence: 99%